Haskap Berry Phenolic Subclasses Differentially Impact Cellular Stress Sensing in Primary and Immortalized Dermal Fibroblasts - Lily R. Zehfus; Zoe E. Gillespie; Carla Almendáriz-Palacios; Nicholas H. Low; Christopher H. Eskiw (Cells, 2021)
It is generally accepted that dietary phenolics from fruits are of significant importance to human health. Unfortunately, there is minimal published data on how differences in phenolic structure(s) impact biological pathways at cellular and molecular levels. We observed that haskap berry extracts isolated with ethanol:formic acid:water or phenolic subclass fractions separated using different concentrations of ethanol (40% and 100%) impacted cell growth in a positive manner. All fractions and extracts significantly increased population doubling times. All extracts and fractions reduced intracellular free radicals; however, there were differences in these effects, indicating different abilities to scavenge free radicals. The extracts and fractions also exhibited differing impacts on transcripts encoding the antioxidant enzymes (CAT, SOD1, GPX1, GSS and HMOX1) and the phosphorylation state of nuclear factor-κB (NF-κB). We further observed that extracts and fractions containing different phenolic structures had divergent impacts on the mammalian target of rapamycin (mTOR) and sirtuin 1 (SIRT1). siRNA-mediated knockdown of SIRT1 transcripts demonstrated that this enzyme is key to eliciting haskap phenolic(s) impact on cells. We postulate that phenolic synergism is of significant importance when evaluating their dietary impact.